Relationship Between Appropriateness Of Medicine Selection And Therapy Outcome In Outpatients Of Hypertension At Dr. Moewardi Surakarta Hospital - Shela Novita Devi; Niken Luthfiyanti; Kharisma Jayak Pratama; Tiara Ajeng L (Media Farmasi Indonesia, 2024)
Hypertension is a degenerative disease characterized by blood pressure that exceeds the standard limit of >140/90 mmHg, which can cause diseases such as heart, eyes, kidneys, brain and blood vessels. Drug selection is one of the factors that is very important because it can help the success of therapy. The purpose of this study was to determine the relationship between the accuracy of drug selection and therapeutic outcomes in outpatient hypertension patients at Dr Moewardi Surakarta Hospital using 100 medical record data with retrospective study and using data analysis techniques in the form of univariate test methods, bivariate tests and chi-square tests . The results showed that patients who received treatment with the suitable indication, right drug, correct dose and proper patient criteria were Ninety-two patients (92%). The relationship between the accuracy of drug selection and therapeutic outcomes in outpatient hypertension patients at RSUD Dr Moewardi Surakarta shows a p-value of 0.030 (p <0.05), so Ho is rejected, meaning that there is a significant relationship in the accuracy of antihypertensive drug selection with therapeutic outcomes in the form of achieving blood pressure targets based on JNC VIII in 2014.